2015
DOI: 10.1007/s00408-015-9794-7
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Survival in Patients with Idiopathic Pulmonary Fibrosis After Lung Transplantation

Abstract: This study demonstrated a 10-year survival time after LTX in IPF. Furthermore, our study demonstrated a significantly better survival after bilateral LTX in IPF compared to single LTX although bilateral LTX patients were significantly younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The primary goal of lung transplantation is to provide a survival benefit for patients with chronic end-stage lung disorders, including IPF. Results from current published articles have implied that there might be a preference to perform DLT for interstitial lung diseases with better survival rates, especially in high-risk patients, young patients, and patients with high mPAP [27,29]. Recently, Villavicencio et al retrospectively analyzed recipients of lung transplants for pulmonary fibrosis between 1987 to 2015, and found that DLT improved survival compared with SLT, which should be considered the procedure of choice in patients younger than 70 years old [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal of lung transplantation is to provide a survival benefit for patients with chronic end-stage lung disorders, including IPF. Results from current published articles have implied that there might be a preference to perform DLT for interstitial lung diseases with better survival rates, especially in high-risk patients, young patients, and patients with high mPAP [27,29]. Recently, Villavicencio et al retrospectively analyzed recipients of lung transplants for pulmonary fibrosis between 1987 to 2015, and found that DLT improved survival compared with SLT, which should be considered the procedure of choice in patients younger than 70 years old [30].…”
Section: Discussionmentioning
confidence: 99%
“…After detailed evaluation, 10 studies were excluded for lacking sufficient data to extract (n = 2), or the survival outcome evaluated in other diseases other than IPF (n = 8). Ultimately, 16 studies with 17,872 IPF cases distributed in five countries were included in this meta-analysis [4][5][6][7][17][18][19][20][21][22][23][24][25][26][27][28] (Fig 1). These studies were published between 2005 and 2019, among which six were single-center studies, while the other ten were multi-center studies.…”
Section: Baseline Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…To date, no randomized controlled studies have weighed the superiority of SLT to BLT in patients with IPF. We compared the data collected at our centre with those published in other countries 10,11,[15][16][17][18][19][20][21][22] (Table 4). Weiss ES and his colleagues reviewed 1256 patients with pulmonary fibrosis and identified that BLT was associated with a lower risk of mortality at 1 year for those with highest LAS.…”
Section: Discussionmentioning
confidence: 99%
“…The unilateral transplant presents fewer perioperative complications than the bilateral one, due to the greater simplicity of the procedure. With bilateral transplantation long-term survival is greater due to greater functional reserve and avoidance of possible complications in the native lung, such as infection and neoplasia [ 42 , 43 , 44 ].…”
Section: Type Of Transplantmentioning
confidence: 99%